South-East Asian populations of Karualona cf. karua (King. 1853) (Crustacea: Cladocera: Chydoridae) belong to a separate species - Sinev, Artem Y.; Semenyuk, Irina I. (Zootaxa, 2023)
Study of populations of Karualona cf. karua (King, 1853) (Сrustacea: Cladocera) from South-East Asia and Sri Lanka revealed that they belong to an undescribed taxon. Karualona fatimae sp. nov. differs from the Australian K. karua s. str. by a very small basal spine of postabdominal claw and the presence of small denticle on the anterior margin of labral keel. The latter character is unique for the genus. Morphology, distribution and phylogenetic position of the new species are discussed. Our data suggest that the diversity of Karualona is underestimated in most tropical regions, with at least one more undescribed taxon present in South-East Asia and one more taxon in Australia. An updated key for genus Karualona Dumont & Silva-Briano, 2000 of the Eastern Hemisphere is provided.